Repositioning Malaysian Chinese Educational Roles in Alignment with One Belt One Road Initiative - Yinghui, Wu; Teng Teng, Yap (Círculo de Lingüística Aplicada a la Comunicación, 2019)
This paper aims to examine the new positioning and new development of Malaysian Chinese educational roles based on the reality with the rise of China, where the Chinese Language has risen in prominence to become a world language. The article points out that it is necessary to reunderstand the advantages of Malaysian Chinese education and re-position its roles due to the inevitable trend of dissemination in the Chinese language to the world. The article suggests that the triple roles of Malaysian Chinese language and the triple functions of Malaysian Chinese education. Malaysian Chinese education should be promoted as a national strategy of Malaysia and to make Malaysia a base to support Chinese education in the nearby countries. Besides, Malaysia should also be a base of Chinese education theoretical construction, standard research and development base, as well as other innovative ideas making for Southeast Asian countries.